Long-Term Aerobic Exercise Enhances Hepatoprotection in MAFLD by Modulating Exosomal miR-324 via ROCK1 - Yang Zhang; Qiangman Wei; Xue Geng; Guoliang Fang (Metabolites)
Background: Insulin resistance (IR) is central to the progression of non-alcoholic fatty liver disease (MAFLD). While aerobic exercise reduces hepatic fat and enhances insulin sensitivity, the specific mechanisms—particularly those involving exosomal pathways—are not fully elucidated. Method: Exosomes were isolated from 15 MAFLD patients’ plasma following the final session of a 12-week aerobic exercise intervention. Liver fat content was measured using MRI-PDFF, and metabolic parameters were assessed via OGTT, HOMA-IR, QUICKI, and VO2 max. Co-culture experiments evaluated the effects of exercise-derived exosomes on IR signaling pathways. miRNA microarray analysis identified miR-324, which was quantified in high-fat diet (HFD) mice with and without exercise and compared between athletes and sedentary controls. Functional assays assessed miR-324’s role in glucose and lipid metabolism, while luciferase reporter and Western blot assays confirmed ROCK1 as its direct target. Result: Aerobic exercise significantly reduced liver fat and improved insulin sensitivity in both MAFLD patients and HFD mice. Notably, exosomal miR-324 levels were lower in athletes than sedentary controls, indicating an inverse association with insulin sensitivity. Post-exercise, precursor and mature miR-324 increased in adipose tissue and decreased in muscle, suggesting its adipose origin and inverse regulation. Functional assays demonstrated that miR-324 modulates insulin resistance by targeting ROCK1. Conclusion: Exercise-induced exosomal miR-324 from adipose tissue targets ROCK1, revealing a novel mechanism by which aerobic exercise confers hepatoprotection against insulin resistance in MAFLD. These findings enhance our understanding of how exercise influences metabolic health and may inform future therapeutic strategies for managing MAFLD and related conditions.